Influência da excentricidade em pilares curtos sob o efeito de flexo compressão normal - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The presented work discusses eccentrically loaded columns under the effect of normal flexural compression. To this end, a database (DB) of tests on short columns under eccentric loads was compiled from national and international technical literature. The study was based on the interaction diagram of the columns' cross-section, addressing their strength through the linear P-m (L) and nonlinear P-m (NL) load-moment relationships, as well as through the simplified methods of NBR 6118 (ABNT, 2023), the standard column method with approximate curvature and approximate stiffness. The performance analysis was based on the χ parameter, which represents the ratio between the experimentally obtained resistant load (DB) and the theoretical load estimates, 𝑃𝑒𝑥𝑝 and 𝑃𝑡𝑒𝑜, respectively. The analysis of the results follows the Collins (2001) criterion, adapted by Moraes Neto (2013), regarding the accuracy and safety of the methods. The results demonstrate that the nonlinear estimate and approximate curvature method showed better performance; however, it is important to note that the standard column method with approximate stiffness also proved to ensure the satisfactory design of short columns under the effect of normal flexural compression, providing both qualitative and quantitative estimates. The results also show that the influence of minimum eccentricity can significantly reduce the load-bearing capacity of the columns, even with low slenderness (short columns), thus always requiring the consideration of first-order minimum eccentricity in the design of eccentrically loaded columns.
Keywords: Pilar curto; Concreto armado; Flexão composta normal; Recomendação de projeto; CNPQ:: CIÊNCIAS EXATAS E DA TERRA